Students' perception toward traditional versus interactive lectures in preclinical operative dentistry course: A comparative cross-sectional study - Marwa Abdalrhman Ahmed; Aliaa Omer Sulaiman; Israa Mohamed Zain; Kamal Mubark Aljack; Elhadi Mohieldin Awooda (Wolters Kluwer Medknow Publications, 2024)
Background: A lecture is one of the most common methods of teaching in higher education. The lecture is generally divided into interactive and traditional. Objectives: This study aimed to assess and compare senior and junior preclinical dental students' perceptions of interactive lectures versus traditional lectures during the preclinical operative course. Materials and Methods: This was a descriptive, comparative cross-sectional study among 100 undergraduate students from Igraa College, Sudan. Students from 2 class years were involved; the first one was batch 2 (semester 6) and the second group was batch 3 (semester 5). Fourteen preclinical operative dentistry lectures were delivered to both classes (7 lectures were interactive and 7 were traditional) during the full-time course. At the end of the course, a self-administered questionnaire included questions about students' demographic data and their perceptions toward traditional and interactive lectures. A comparison between different nonparametric data was done by Chi-square test with the level of significance set at P < 0.05. Results: The response rate was 77%, where male students were 26 (33.8%) and female students were 51 (66.2%). There was no statistically significant difference between sex and class year in terms of the student's preference for the types of lecture. Female students 42 (54.5%) and male students 24 (31.2%) agreed that interactive lectures increase focus on the material more than traditional lectures. The majority of students from both class years agreed that interactive lectures help them in leadership skills 58 (75.4%) and improving their communication between professors and students 65 (84.4%). Conclusions: interactive teaching has been greatly accepted by students who were accustomed to traditional teaching with differences in the preference of either type of lecture.